1988
DOI: 10.1152/jappl.1988.65.5.2107
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary gas exchange in Andean natives with excessive polycythemia--effect of hemodilution

Abstract: Pulmonary gas exchange in Andean natives (n = 8) with excessive high-altitude (3,600-4,200 m) polycythemia (hematocrit 65.1 +/- 6.6%) and hypoxemia (arterial PO2 45.6 +/- 5.6 Torr) in the absence of pulmonary or cardiovascular disease was investigated both before and after isovolemic hemodilution by use of the inert gas elimination technique. The investigations were carried out in La Paz, Bolivia (3,650 m, 500 mmHg barometric pressure). Before hemodilution, a low ventilation-perfusion (VA/Q) mode (VA/Q less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…28,54 Afterward, Bolivian investigators reported 2 studies. 55,56 Further cardiac catheterization studies on CMS have not been performed in the Andean region. Chinese and Kyrgyz investigators have also published interesting observations on CMS and related diseases, as discussed in the following sections.…”
Section: Chronic Mountain Sicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…28,54 Afterward, Bolivian investigators reported 2 studies. 55,56 Further cardiac catheterization studies on CMS have not been performed in the Andean region. Chinese and Kyrgyz investigators have also published interesting observations on CMS and related diseases, as discussed in the following sections.…”
Section: Chronic Mountain Sicknessmentioning
confidence: 99%
“…Ergueta et al found average values of Hb 26 g/dL, PPA 51 mm Hg, and SaO 2 84% in 2 patients studied in La Paz. 55 Manier et al reported Hb 21Ϯ1 g/dL and PPA 56 Chinese investigators have made important clinical and epidemiological studies in the last 2 decades. There are limited observations of pulmonary hemodynamics, however.…”
Section: Cardiac Catheterization and Pulmonary Hemodynamics In Cmsmentioning
confidence: 99%
“…MONGE and WHITTEMBURY [56] described a syndrome marked by the triad of polycythaemia, hypoxaemia and impaired mental function in which affected individuals complain of headache, fatigue, impaired concentration, irritability and impaired exercise tolerance, and physical examination demonstrates clubbing, congested mucosal surfaces and cyanosis. Treatment involves relocation to lower elevations or, in cases where relocation is not feasible, periodic phlebotomy [57], isovolaemic haemodilution [58,59] and long-term use of respiratory stimulants such as acetazolamide [60] or medroxyprogesterone [61]. Right heart failure was not described in the report by MONGE and WHITTEMBURY [56], but has subsequently been described in advanced stages of the disease in populations outside the Andes [62].…”
Section: High-altitude Illnessmentioning
confidence: 99%
“…89,90 The degree to which elevated pressures and reduced cardiac output in CMS are due to polycythemia, and its associated hyperviscosity has been studied with isovolemic hemodilution. 91 In this study of 8 subjects with CMS and Hb greater than 19 g/dL, normovolemic phlebotomy lowering the Hb content from 21.5 to 18.2 g/dL had a reduction of PVR from 3.9 to 3.1 Wood units. The fall in mean PAP was less (27 to 25 mm Hg) because the cardiac output rose considerably from 5.5 to 6.9 L/min.…”
Section: 77mentioning
confidence: 60%
“…Isovolemic phlebotomy safely reduces hematocrit, improves ventilation, improves arterial saturation, and decreases PAP. 91 Ventilatory stimulants such as acetazolamide 250 mg/day increase ventilation during sleep and wakefulness and increase oxygen saturation with a drop in erythropoietin, hematocrit, and a reduction of symptoms. 95,96 Two recent randomized controlled trials showed that treatment for 3 months reduced PVR, increased cardiac output, and maintained oxygen delivery despite a 6% to 10% fall in hematocrit.…”
Section: Treatment Of Cmsmentioning
confidence: 99%